2021
DOI: 10.1007/s10653-021-00874-6
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of essential elements in volcanic soils: potential harmful health effects on grazing cattle

Abstract: Several essential nutrients such as Fe, Co, Cu, I, Se, and Zn are vital to grazing cattle as they play a significant role in intracellular enzyme systems, with antioxidant and repair functions of DNA lesions. Feeds may supply most essential nutrients in adequate amounts. However, essential nutrient deficiencies are common and are mainly related to the geochemical characteristics of the soils, inherited from parent rocks. This study aims to assess the concentrations of the selected essential nutrients in topsoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…These results agree with those previously published by Pinto (2007a,b), which revealed a general deficiency of TE in grazing cattle in most of the Azores' islands, which can be associated with the characteristics of the volcanic soils existing here. Linhares et al (2021) reported that in S. Miguel, the concentrations of Cu and Zn are insufficient to cover the minimum needs of ruminants, while Fe, Co, Cu, I, and Zn in the soils and pastures of this same island of the Azorean archipelago exist in very low concentrations. For animals into which TMBs were introduced, a significant increase (P < 0,05) in the mean concentration of Cu and Se was observed on the parturition day and 60 days after.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results agree with those previously published by Pinto (2007a,b), which revealed a general deficiency of TE in grazing cattle in most of the Azores' islands, which can be associated with the characteristics of the volcanic soils existing here. Linhares et al (2021) reported that in S. Miguel, the concentrations of Cu and Zn are insufficient to cover the minimum needs of ruminants, while Fe, Co, Cu, I, and Zn in the soils and pastures of this same island of the Azorean archipelago exist in very low concentrations. For animals into which TMBs were introduced, a significant increase (P < 0,05) in the mean concentration of Cu and Se was observed on the parturition day and 60 days after.…”
Section: Resultsmentioning
confidence: 98%
“…Soil-climatic conditions and fertile soils of volcanic origin allow the Azores to present excellent conditions for creating dairy and beef cattle based on pastures throughout the year. However, cattle grazing in the Azores lacks some essential TE such as cobalt, copper, iodine, selenium, and zinc (Pinto et al 2007a,b), because of the low levels of these elements in the pasture due to the volcanic genesis of Azorean soils (Linhares et al 2021), compromising the normal functioning of the body which can cause health problems for cattle, specifically in terms of the immune and reproductive systems (Suttle 2010). Particularly in heifers, it has been demonstrated that TE are crucial for the reproductive apparatus development, keeping animals healthy and well prepared for their first lactation.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the Cu content found in Asparagopsis taxiformis (7.41 ppm) was 43% less than that found in Asparagopsis armata (12.99 ppm). The trace elements present in fresh seaweed may constitute an important source for the natural supplementation of trace elements for ruminants in the Azores, since there are recently published studies, such as SREAC [ 2 ] and Linhares et al [ 29 ], indicating a generalised deficiency of trace elements in Azorean cattle, among which are manganese and copper, with the values found in both seaweeds exceeding the minimum needs required by dairy cattle [ 30 ], when considering the analysed values per gram of dry matter (g/DM). However, it is important to note that the adequacy of these trace elements to meet the minimum requirements of dairy cows depends on the quantity of seaweed consumed and the bioavailability of these trace elements in digestion, which was not evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%